2018
DOI: 10.1021/acs.jced.8b00874
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Diatomite–Carbon Nanotube Composite Adsorbent and Its Adsorption Characteristics for Phenolic Compounds

Abstract: Carbon nanotubes (CNTs) were synthesized on a Ni catalyst−diatomite substrate using a chemical vapor deposition (CVD) method. By controlling the synthesis conditions, we explored the influence of synthesis time and temperature on the synthesis of CNTs. The carbon yield and microstructure of the resulting CNTs were investigated by thermogravity (TG), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Raman spectroscopy analysis. Then, two kinds of purification methods, annealing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…As the major constituent of diatomite is bio‐SiO 2 , [19] so it is ineluctable to compare the activity difference with commercial SiO 2 . KOH/diatomite and KOH/SiO 2 catalysts were prepared for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…As the major constituent of diatomite is bio‐SiO 2 , [19] so it is ineluctable to compare the activity difference with commercial SiO 2 . KOH/diatomite and KOH/SiO 2 catalysts were prepared for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the removal of phenolic compounds from the contaminated water on a large scale is necessary for a healthy life. For this, CNTs with rich pore structure, analytic abilities, high surface area, and sharp curvatures show great potential for the removal of the phenolic compounds from the contaminated water through π-π, electrostatic, hydrophobic, and hydrogen bonding interactions [138]. Ma et al have prepared CNTs/Fe@C hybrids material for the removal of the binary dye from the contaminated water through the one-pot method with a high specific surface area (186.3 m 2 /g).…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…As reported by other researchers, the composite seems to possess a higher adsorption capacity owing to the combination of the advantages of CNTs and other absorbents. Wang et al synthesized CNTs on the diatomite to form a composite adsorbent for the elimination of phenol from water, and the results showed that the uptake amount of phenol by the composite significantly increased [ 23 ]. However, these materials used as the substrate for the CNTs’ growth need to be pretreated by being coated with a catalyst such as ferric nitrate, nickel nitrate or cobalt nitrate.…”
Section: Introductionmentioning
confidence: 99%